Techno-economic analysis of adiabatic four-stage CO2 methanation process for optimization and evaluation of power-to-gas technology. (15th June 2021) - Park, Sungho; Choi, Kwangsoon; Lee, Changhyeong; Kim, Suhyun; Yoo, Youngdon; Chang, Daejun
Abstract: Owing to increasing demands for clean energy, caused by global warming, renewable energy sources have attracted significant attention. However, these sources can affect the reliability of electrical grids owing to their intermittency. Power-to-gas technology is expected to help address this issue. In this study, the CO2 methanation process, which yields synthetic natural gas (SNG) via the synthesis of CO2 and H2 through proton exchange membrane (PEM) water electrolysis using surplus electricity generated from renewable energy, was evaluated and optimized based on techno-economic analyses. Requirements for the introduction of SNG produced through CO2 methanation in domestic natural gas markets are presented by considering various scenarios. Results indicate that, even if the electricity costs, including system marginal price and renewable energy costs, are minimal, the costs for PEM water electrolysis and CO2 methanation must be reduced by ~$550/kW and 25%, respectively, relative to current levels for the viable introduction of SNG in domestic markets. Highlights: Techno-economic analysis was performed for optimization of CO2  methanation. The optimal design point of CO2  methanation process was presented. Price criteria of synthetic natural gas was proposed to enter the domestic market.